REKONSTRUKSI PEMBENTUKAN KARAKTER PESERTA DIDIK ERA GENERATIVE ARTIFICIAL INTELLIGENCE PERSPEKTIF FILSAFAT PENDIDIKAN AL-GHAZALI - Ririn Mu'tamiroh, Siti; Mu’allimah; Ihda Maulidya Khothrun Nabila; Ari Abi Aufa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Generative Artificial Intelligence (Generative AI) has brought significant changes to the field of education, including the process of students' character development. The ease of access to information and the automation of learning provide numerous benefits; however, they also pose challenges, such as declining academic integrity, responsibility, and independent learning. This study aims to reconstruct the concept of students' character development in the era of Generative AI from the perspective of Al-Ghazali's philosophy of education. The research employed a qualitative approach using a library research method. Data were collected from Al-Ghazali's works, books, scholarly journal articles, and relevant documents discussing Islamic educational philosophy, character education, and Generative AI. The data were analyzed through data reduction, data presentation, thematic analysis, and conclusion drawing. The findings indicate that Al-Ghazali's educational philosophy, which emphasizes tazkiyat al-nafs (purification of the soul), moral character development, adab (ethical conduct), exemplary behavior, and habituation, remains highly relevant in addressing the challenges of the artificial intelligence era. Therefore, the reconstruction of character education in the era of Generative AI should integrate the use of technology with Islamic spiritual, moral, and ethical values to enable students to utilize AI wisely, responsibly, and with noble character.